Single-Period Inventory Models with multiple ordering opportunities: A review - Kalpana, P.; Kaur, Arshinder (Inderscience Publishers, 2012)
Single-Period Inventory Models (SPIMs) or else referred as newsboy model are used to acquire optimal ordering decisions of short life-cycle products facing uncertain demand. Due to longer production and delivery lead-time, SPIM have single-ordering opportunity. To reduce the higher demand variability, the concept of SPIM with multiple ordering opportunities has been adopted in the recent literatures and has proved that the supply chain performance is better than SPIM. This paper broadly studies the literature discussing the SPIM with multiple ordering opportunities under three major classifications such as 1 ordering and pricing scenarios 2 methodologies adopted and 3 demand information updating. This paper identifies several research gaps from the existing literatures and proposes a conceptual model based on those gaps. This study also suggests some potential scope for research.